RANCANG BANGUN APLIKASI DATA KEPEGAWAIAN BERBASIS WEB MENGGUNAKAN METODE WATERFALL - Sandy, Muchamad; Lazuardi, Sandi Nuramadhana (Jurnal Tera, 2024)
Human resource information systems (HRIS) are essential for effective business operations today. To address this need, this research aimed to design a web-based HRIS that could be implemented in any organization. The Waterfall methodology was employed for this development. The Waterfall model, a linear sequential design approach, was chosen due to its simplicity and suitability for smaller projects. The results demonstrated that the Waterfall method could be successfully applied to the design of this specific HRIS